A View to Interlanguage and its Impact in the Development of L2 Writing Skills in a Group of Fourth Semester Students of Modern Languages at the University of Quindío (2016)
Interlanguage is understood as a linguistic system which is inherently built upon the growing knowledge of a second language (L2) and that of the one already acquired that is basically known as the mother tongue or L1. Relevant here is to know that the learner happens to be the center of the SLA process and his performance is fundamental at the time of noticing such phenomenon. Therefore, the present study aims to identify and examine the notion of interlanguage and the way it influences the learners’ performance, especially in written contexts. As there are both advantages and disadvantages, the major focus of this study is to shed light on the L1 negative transfer through an error analysis of written assignments in a group of fourth semester students at the University of Quindío. Additionally, a focus group and an interview were carried out as a way of strengthening this investigation. As the research project took the shape of a case study, it was convenient to analyze the collected data under qualitative standards. Since there is little knowledge and awareness when it comes to this issue, it is of paramount importance to undertake an investigation on this subject matter. Undoubtedly, the results achieved come to provide enough evidence to confirm that there is indeed an L1 interference which affects directly the L2 learners’ written production. Furthermore, such results serve as a way to broaden some perspectives with respect to interlanguage as a prevalent factor to which attention must be given, primarily in academic environments.